What Happens in Savannah Shouldn’t Stay in Savannah - Dean Luethi (Academic Chairpersons Conference Proceedings, 2020)
Each of us attend conferences with the best intentions of learning something new and utilizing this knowledge when we return to our routine. We often fall short. Participants will discuss strategies to integrate their newfound knowledge into their lives back home and make a plan to actualize that desire.
Keywords: Education; knowledge; skills; productivity; efficiency